2017
DOI: 10.1039/c7nr04353h
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime nanomanometry – high-pressure luminescence of up-converting lanthanide nanocrystals – SrF2:Yb3+,Er3+

Abstract: Anti-Stokes luminescence of up-converting nanocrystals SrF:Yb,Er can be used as a high pressure optical sensor alternative to the ruby fluorescence-scale. In nanocrystalline SrF:Yb,Er, high pressure reversibly shortens the emission lifetimes nearly linearly up to 5.29 GPa at least. Its advantage is the use of NIR (≈980 nm) radiation, highly penetrable for many materials. The shortening of up-conversion lifetimes has been attributed mainly to the changes in energy transfer rates, caused by decreased interatomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
122
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(123 citation statements)
references
References 46 publications
1
122
0
Order By: Relevance
“…In addition, after an ultrahigh‐pressure compression and release circle, the upconversion luminescence spectra were measured again for the second circle under pressure of R0.00→5.03 GPa where the luminescence intensity still exhibits an enhancement, indicating that the coordination environment of the luminescent ions within the crystallographic structure of the host lattice is retained even an ultrahigh pressure of up to 22.98 GPa is applied. However, the emission intensity was only improved to about 50% of that measured in the first compression cycle at 6.01 GPa (Figure b), which is probably due to the crystal defects formed during compression and release process, which leads to the weakened luminescence intensity …”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…In addition, after an ultrahigh‐pressure compression and release circle, the upconversion luminescence spectra were measured again for the second circle under pressure of R0.00→5.03 GPa where the luminescence intensity still exhibits an enhancement, indicating that the coordination environment of the luminescent ions within the crystallographic structure of the host lattice is retained even an ultrahigh pressure of up to 22.98 GPa is applied. However, the emission intensity was only improved to about 50% of that measured in the first compression cycle at 6.01 GPa (Figure b), which is probably due to the crystal defects formed during compression and release process, which leads to the weakened luminescence intensity …”
Section: Resultsmentioning
confidence: 84%
“…Compared to the above endeavors, hydrostatic pressure could offer unique merits to regulate and explore the luminescent properties, especially of upconversion luminescent materials, which is growing as a prevalent topic . The tunable hydrostatic pressure can be utilized not only to probe the crystal structure and coordination bonding information of luminescent materials, but also to influence the electronic state and/or crystal field symmetry of luminescent ions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result may be important for low-pressure sensing. Runowski et al [120] reported a lifetime nanomanometry based on SrF 2 :Yb/Er upconverting nanocrystals, utilizing the reversible and nearly linear shortening of the emission lifetimes at increased high pressures.…”
Section: Stress Sensingmentioning
confidence: 99%
“…Fluoride compounds are potential hosts for luminescent materials due to their suitable chemical stability and excellent luminous properties, and as such, have received a lot of attentions over the past few decades. [1][2][3][4] Cryolite is an important kind of uoride compound, the chemical formula of which can be expressed as M 3 NF 6 , where M represents monovalent cations such as alkali metal ions (Li + , Na + , K + , Rb + ) and NH 4 + , and the sites of N can be occupied by trivalent cations, that is Al 3+ , Y 3+ , Sc 3+ , Ga 3+ , etc. 5,6 In addition, the N sites can also be occupied by rare earth ions by isomorphic replacement in the cryolite lattice, such as K 3 GaF 6 , 7 K 3 InF 6 , 8 and K 3 LuF 6 .…”
Section: Introductionmentioning
confidence: 99%